EFFECT OF STUDENTS’ LEARNING INTERESTS, ATTITUDES, AND PERCEPTION ABOUT TEACHER’S TEACHING TECHNIQUE TOWARD MATH LEARNING OUTCOMES IN CLASS VIII SMP NEGERI IN THE DISTRICT BULUKUMBA - Lilis Erviana (USN Kolaka, 2016)
The influence of students’ learning interest, attitude, and perception on teacher’s teaching technique toward math learning outcome of the Eight Grade Students at State Secondary Schools in Bulukumba. Mathematics learning outcomes one of measuring tools to know the quality of a mathematics learning outcomes; however; this research is limited into learning interest, attitude, and student’s perception on teaching method. It aims to reveal the influences of learning interest and student’s perception on teaching method toward students’ mathematics learning outcomes both directly and indirectlythrough attitude to mathematics subject of the eight grade students at state secondary schools in Bulukumba. Population of this research was 235 students at class VIII of 34 state secondary schools in Bulukumba, in academic year of 2013/2014 which included in A, B, and C accreditation. The sample was taken though proportional stratified random sampling. Moreover, the instruments used in this research were: 1)scale of learning interest, 2) scale of student’s perception on teaching method, 3) scale of attitude in mathematics aa well as mathematics learning outcome test. Data analysis applied a descriptive statistics and SEM (Structural Equation Modeling) analysis. The result shows that: 1) most of eight grade students of state secondary school in Bulukumba have 84% students with a good learning interest, 76.5% of them have a good perception on teaching method, and 77% of them have a good attitude to the mathematics subject; 2) learning interest and student’s perception have a significant positive influence to the attitude in mathematics learning; 3) learning interest, students perception on teaching method, and attitude toward mathematics subject has a significant positive influence toward mathematics learning outcomes; 4) learning interest has a significant positive influence to the student’s perception on teaching method; 5) learning interest has a significant positive influence indirectly though the attitude toward mathematics learning outcomes; and 6) students’ perception on teaching method has a significant positive influences indirectly through the attitude toward mathematics learning outcomes.